The story of the colony : a structure celebrating the triumphs of technology. - Antonov, Viktor, ....- (Culver City : Designstudio, 2010)
The Colony is the lavishly-illustrated fictional tale of Gabriel Duban's epic journey to discover the truth about a lost city, in 1875. With antiquated colour illustrations, the reader is guided through a world of adventure and horror which celebrates the triumphs of technology and colonialism. This feast for the eyes and the mind is a treat for readers and fans of fine art.
Keywords: kolonialisme